Integrated Methodology for Efficient Sizing of Investments in Transport Infrastructure - Frantz Daniel FISTUNG; Cornelia NEAGU; Marius BULEARCĂ; Cristian SIMA (Communications of International Proceedings, 2025)
The purpose of this paper is to present an integrated analysis methodology that is more appropriate in most cases where a decision must be made regarding the correct and profitable sizing of investments in transport infrastructure. The methodology analysed proposes three distinct stages, namely: Sizing investments for the current year; Evaluating replacement (renewal) costs; Sizing operational and maintenance expenses. Based on the proposed methodology, the specific elements for calculating infrastructure investments are presented in detail for each mode of transport. The final part of the paper presents examples of calculating the investment needs for transport infrastructure, currently adopted in several European countries.
Keywords: Transport infrastructure; investment policy; investment efficiency methodology